Beginning Object Oriented ASP.NET 2.0 with VB.NET - Myers, Brian R. (Apress, 2012)
This book was born out of a lunch that I had with two colleagues of mine. They both had an extensive background in mainframe development, but they were struggling to understand what OOP was and how they should apply it. During the conversation, I explained some of the basics of OOP and afterwards thought about better ways to teach these developers the concepts of OOP. That lead me to decide that I should write a book, which lead me to Apress—and the rest is history. Object-Oriented Programming is important in today’s ever-changing world. More and more businesses are abandoning mainframe development for client/server development. Client/server development is greatly enhanced by OOP techniques. OOP techniques teach developers to build reusable code and to think about a problem in terms of the real world. OOP is all about modeling the real world to make more user- and business-friendly software applications.